Changes in cyclic hydroxamic acid content of various rye varieties for the effect of abiotic stress - Makleit, Peter (Acta Biologica Szegediensis, 2005)
According to our opinion cyclic hydroxamic acids (cHx-s) are stress metabolites. For the effect of stress the level of cHx rises and through their various biological effects the cHx-s prevent the plants from the harmful influences of stress. In these experiments I examined the changes in cHx-content of rye plants (Secale cereale and S. cereanum varieties). The plants were grown in nutrient solution and were treated with 100mM NaCl. My hypothesis in the case of shoots was proved: the cHx-content of shoots of all varieties changed according to stress syndrome. I could not demonstrate early decrease in cHx-content of roots, but I suppose that it had occurred before my first observation.